Status of shrimp production in Malaysia with an emphasis on overexploited species - Izzuddin, Mohd Haikal; Rahman, Mohammad Mustafizur (2019)
Malaysia is surrounded by a large waterbody, which is very rich in various fisheries resource including a wide variety of shrimps. In Malaysia, shrimp production is very important in terms of food supply, contributing to gross domestic product (GDP) and employment. Demand on Malaysian shrimp is gradually increasing starting from 19th century when aquaculture is starting to be popular. Presently, Malaysia is one of the 9th largest shrimp exporter in the world. Malaysia produced a total of 84 thousand tones shrimp in 2017. The capture production of shrimp in Malaysia is almost stable. Although aquaculture production of shrimp in Malaysia is increasing every year, the capture production still contributes nearly half (45%) of total shrimp production. The actual might be higher than the recorded production as the catchment of each individual species is not available. In 2017, the production of freshwater shrimp was 803 tons, which contributed only 1% in total shrimp production. The main contributing species in capture production is sergestid shrimps, which contributed 98.7% of the total capture shrimp production. The rest of the capture production came from freshwater shrimp species. In Malaysia, the aquaculture production mainly comes from giant river prawn (Macrobrachium rosenbergii), giant tiger prawn (Penaeus monodon) and whiteleg shrimp (Litopenaeus vannamei). The highest shrimp aquaculture production comes from whiteleg shrimp (contributes 89% of total farmed shrimp production) followed by giant tiger prawn (10%) and giant freshwater prawn (1%). Penaeus Indicus and Parapenaeopsis spp. and other wild shrimp harvest will eventually depleted in number as their stock rely solely on wild population. Parapenaeopsis spp. is one of regular shrimp species, which has low market price, and are available in the market throughout the year, making it one of the most consumed shrimps by Malaysian. However, studies on wild species of shrimp in Malaysia is very lacking. The population may be in risk of overharvesting if they are not well managed, although regulation on catching was already being introduced, several other aspects also need to be considered... Regular data collection and their analysis are very important to prepare management guidelines for their sustainable capture production.